Corticosteroids - Gamal Al-kaf, Ali (IntechOpen, 2018)
Corticosteroids are mainly used to reduce inflammation and suppress the immune system. Corticosteroids will only be prescribed if the potential benefits of treatment outweigh the risks. They will also be prescribed at the lowest effective dose for the shortest possible time. This book will strive to highlight the importance of corticosteroids, to focus on minimizing side effects, to monitor and sensitize the population on the potential adverse effects of misuse, to provide additional knowledge about the design and development of new drug delivery systems loaded with corticosteroids potentially useful in the treatment of chronic inflammatory-based diseases, and to reduce inflammation and affect the immune system. The major objective of this book will be to present the information in a lucid, condensed, and cohesive form and to specially cater to the needs of readers in medicine and pharmacy.